Comparison of the AIMS65 Score with Other Risk Stratification Scores in Upper Variceal and Nonvariceal Gastrointestinal Bleeding. - Alexandrino, G (2019)
Submitted by arminda sustelo (arminda.sustelo@hff.min-saude.pt) on 2019-02-22T12:01:33Z No. of bitstreams: 1 Gut Liver. 2018.pdf: 233789 bytes, checksum: bbe4a606484ac80bb82223a47e0e6d05 (MD5)